A Lewisian Trilemma. (3rd November 2013) - Stefánsson, H. Orri
Abstract According to one reading of the thesis of Humean Supervenience, most famously defended by David Lewis, certain 'fundamental' (non‐modal) facts entail all there is but do not supervene on less fundamental facts. However, in this paper I prove that it follows from Lewis' possible world semantics for counterfactuals, in particular his Centring condition, that all non‐modal facts supervene on counterfactuals. Humeans could respond to this result by either giving up Centring or abandoning the idea that the most fundamental facts do not supervene on less fundamental facts. I argue that either response should in general be acceptable to Humeans: the first since there is nothing particularly Humean about Centring; the latter since Humeans should, independently of the result I present, be sceptical that the supervenience of one fact upon another by itself says anything about 'fundamentality'.1